Peirce's resonances on Deleuze's concept of sign: Triadic relations, habit and relation as semiotic features - Cardoso, Helio Rebello [UNESP] (Walter De Gruyter Gmbh, 2018)
This article inspects Peirce's resonances on Deleuze's semiotic. Whereas most of the literature agrees that Deleuze adapts Peirce's semiotic to serve his Bergsonian-based theory of sign, this article claims that the relationship of Deleuze with Peirce's writings is more foliated than it may appear at first. The development of this hypothesis invites to trace back Deleuze's works before his very acquaintance with Peirce in the 1980s. Therefore, one of Peirce's classical issues the role that relations and habits play for the triadic conception of sign - is considered with Deleuze's early studies, in which he developed this same issue as to approach Hume (habit and relation, 1953) and Proust (triadic sign, 1964). This background echoes years later in Deleuze's incursion to Peirce's semiotic in the 1980s ninety-two classes and two books on cinema. In fact, Deleuze's own triadic conception of sign and his acknowledged pragmatist inclination prove to be closer to Peirce's pragmatismthan the scholarly literature tends to think or argue. The aim of this article is not, however, to build an overwhelming philosophical identity between Deleuze and Peirce, it sets up instead a steadier basis from where to understand their differences. Deleuze's ignored five-year long lectures on cinema shows to be exegetically revealing with respect to his debts towards Peirce.
Keywords: Deleuze; Peirce; sign; triadic; relation; habit